Medical Applications at CERN and the ENLIGHT Network - Dosanjh, Manjit; Cirilli, Manuela; Myers, Steve; Navin, Sparsh (Frontiers in Oncology, 2016)
State-of-the-art techniques derived from particle accelerators, detectors, and physics computing are routinely used in clinical practice and medical research centers: from imaging technologies to dedicated accelerators for cancer therapy and nuclear medicine, simulations, and data analytics. Principles of particle physics themselves are the foundation of a cutting edge radiotherapy technique for cancer treatment: hadron therapy. This article is an overview of the involvement of CERN, the European Organization for Nuclear Research, in medical applications, with specific focus on hadron therapy. It also presents the history, achievements, and future scientific goals of the European Network for Light Ion Hadron Therapy, whose co-ordination office is at CERN.